Illegal immigration: an analysis of factors and effects - CHINAR, Saadane; ZIBAR, Chadli (Journal of Human Sciences, 2025)
The article addresses the issue of illegal immigration, highlighting its factors and effects. The article is divided into two main parts: the first focuses on the factors of illegal migration, which include internal factors such as poverty, unemployment, and insecurity, and external factors such as economic disparities between developed and developing countries, in addition to geographical and historical proximity between source and destination countries. The second part addresses the impacts resulting from illegal immigration, including positive and negative impacts on both source and destination countries. Among the positive effects we find financial transfers that contribute to supporting the local economy, while the negative effects include increased pressure on social services in destination countries and higher crime rates.